FRAMEWORK FOR FINANCING SOCIAL HOUSING: EUROPEAN BEST PRACTICES - ZATONATSKA, Tetiana; ANISIMOVA, Olga; PASHKEVYCH, Yegor; TARANENKO, Victoriia; KORIAHINА, Tetyana (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article analyzes various mechanisms used in European countries to finance social housing. Social housing is one of the methods of state assistance to vulnerable groups of the population. It allows to stimulate the development of certain regions, and also ensures the attraction of personnel to critical infrastructure facilities. It has been established, that European countries use different mechanisms for financing social housing. The choice of mechanisms depends on the GDP of the country itself, the structure of revenues and expenditures of the state and local budgets, and the availability of funds in individual territorial communities. It has been found that, depending on the social policy pursued by the country, social housing can be financed at the expense of local budget revenues, grants from individuals and corporations, and a combination of these sources.It is established that the concept of social housing in the country is developing gradually. This is due to the fact that at the initial stages, the state uses social housing to stimulate certain regions and attract specific specialists in urgent need. With the growing demand for social housing, territorial communities are increasingly facing problems with available resources, so they are beginning to look for other mechanisms to attract funding. In particular, other financing mechanisms involving private capital have recently been actively developing in European countries, which will partially cover the population's housing costs and speed up this process without additional costs for local authorities. It is found that the situation in Ukraine requires the creation of a fundamentally new mechanism that will help different segments of the population affected by the aggression, direct efforts to rebuild the destroyed regions and attract external resources to optimize this process.
Keywords: social housing; financing mechanism; municipal social housing; grants for social housing; support for vulnerable groups of the population